Necrotizing Periodontal Diseases in a Semirural District of South Africa - Neil Hamilton Wood; Elaine Blignaut; Johan Lemmer; Robin Meyerov; Liviu Feller (AIDS Research and Treatment)
Objectives. The aim of this study was to characterize the lesions of necrotizing gingivitis (NG) and necrotizing periodontitis (NP) with regard to extent and severity, and to correlate these parameters with the host HIV serostatus, CD4+ T-cell count, neutrophil count, age, and gender. Methods. Eighty-four consecutive patients, 39 black females and 45 black males aged 20–46 years, diagnosed with NG/NP were recruited to the study over a period of two years. Results. For both HIV-seropositive and -seronegative patients, the mandibular anterior gingiva was most frequently affected; 74% had NG/NP affecting ≥5 gingival tooth sites. Ninety percent of all patients had a mean severity of ≤4 mm. There was no statistically significant association between either extent or severity of NG/NP and HIV serostatus, CD4+ T-cell count, neutrophil count, age, or gender. The difference between the number of HIV-seropositive patients with NG/NP who had CD4+ T-cell counts ≤200 cells/mm3 and those who had CD4+ T cell counts of 201–499 cells/mm3 was not statistically significant. Conclusion. The clinical signs of NG/NP are similar in HIV-seropositive and -seronegative patients, and are not related to CD4+ T-cell count, to neutrophil count, to gender, or to age.